(untitled) (Bulletin KNOB, 1993)
The dendrochronological dates have invariably been related to existing historical and art-historical Information on the buildings in question. In some cases the data on this were only discovered later, such as on the castle of Rechteren in Dalfsen, the main building of which had been dated dendrochronologically before, in 1505. This building date now seems to be connected with the enforced removal of the lord of the castle. From dendrochronological dates established in the town of Utrecht it became apparent once again that gouged out counting marks are to be expected there, as well as in South Holland, as early as in the third quarter of the fifteenth century. The taking and preparing of wood samples was invariably executed by the RDMZ in Zeist; other persons and institutions were also involved in measuring the tree-rings and dating them. A number of datings took place at the request of the ’Vereniging Hendrick de Keyser’ (Hendrick de Keyser Association), which is to publish the first part of the revised book Het Nederlandse woonhuis van 1300-1800 (The Dutch private house from 1300-1800), written in 1969 by Meischke and Zantkuijl.